B for Brexit: a survey of the economics academic literature - Campos, Nauro F. (Bonn, 2019)
"This paper surveys the economics academic literature on Brexit. It is organised in: pillars, channels, and consequences. The two building blocks to understand Brexit are the economic history of the UK-EU relationship and the literature on the political economy of globalisation and populism. The paper then reviews the evidence on the standard mechanisms through which the UK benefited from EU integration (trade, migration and FDI). Next it surveys the short-run effects of the vote and discuss expected long-term consequences of "Brexit proper." It concludes by identifying some main gaps in the economics literature on Brexit."